Uma tessitura entre saberes e práticas : rabiscos sobre o estigma, a produção de cuidado e a formação dos profissionais da saúde na atenção ao suicídio - Xavier, Danielly Abreu (2018)
The aim is to analyze qualifications offered to healthcare professionals that nurse people with suicidal matters, emphasizing the field of public politics established in Brazil. The research was carried out through a narrative review of literature and taking the following analysis corpus: scientific journals published on the mainstream electronic data of the Virtual Health Library (BVS), such as Medline and Lilacs; journals from the Coordination for the Improvement of Higher Education Personnel (CAPES); academic papers from the Brazilian Digital Masters and Doctoral Thesis Library (BDTD); books, master´s thesis, governmental reports as well as other references used along the papers, in articulation with the researcher’s own career. The data were used through the modality of theme analysis. The categories addressed in this study are stigma and taboo, care giving production, suicide prevention and professional qualification. The dialog of the research and the theme was held within the pillar of Live Work Micro politic in Act, from the theoretical Merhy (2003; 2007) and his dialogue with other authors. Regarding the healthcare professional, it was determined that their profile interferes directly on the production of the giving care offered to the ones with suicidal behavior, including stigmatization. The strengthening and establishment of the principles and guidelines of health politics, including politics to prevent suicide, challenge both professionals and managers, since the identification of health sphere real needs detaches from the intent to elaborate new strategies the yields full heath issues. Within this context, the qualification and engagement of the health professionals becomes more than a strategy, but a stand toward life. The specific qualifications about suicide issues can be reached by securing permanent education as a method for promotion and prevention embedded on these professionals daily life.